Competition, new management practices and the emphasis given to non-financial indicators in manufacturing organizations / Mohd. Yussoff Ibrahim, Daing Nasir Ibrahim and Subramaniam Pillay - Ibrahim, Mohd. Yussoff; Ibrahim, Daing Nasir; Pillay, Subramaniam (Faculty of Business and Management ; UiTM Press, 2002)
This paper reports the result of an empirical study examining the linkages between the intensity of competition (COM), adoption of new management practices (NMP) and the emphasis given to non-financial indicators in decision-making (ENFI) in manufacturing companies. In this study NMP is viewed as a phenomenon influenced by COM and at the same time impacts ENFI. Two issues focused in this study are: does competition compel managers to adopt more of the new management practices and does the increase adoption of the new management practices induce managers to use more NFI in decision making? Should both linkages prove significant, we can possibly deduce that adoption of the new management practices could be the variable that link competition to ENFI. The data from 105 Malaysian manufacturing companies was analyzed using the correlation and regression analysis. The results of both analyses indicate that both the relationships are positive and significant. This study does not reject the possibility that the adoption of the new management practices is what cause management to emphasize NFI during the period of intense competition.